The Making of an American Thinking Class : Intellectuals and Intelligentsia in Puritan Massachusetts. - Staloff, Darren (Oxford University Press, 1997)
This is a reinterpretation of the political and intellectual history of Puritan Massachusetts, envisioning the Bay colony as a 17th-century one-party state. The author argues that ideologies, as well as ideological politics, are produced by self-conscious and class-conscious thinkers.